Predictive Value of Cerebrospinal Fluid Biomarkers for Tap Test Responsiveness in Patients With Suspected Idiopathic Normal Pressure Hydrocephalus - Hua, Rongrong; Liu, Chunyan; Liu, Xing; Zhu, Jinwu; Zhang, Jie; Wang, Lidong; Shi, Zhe; Li, Jian; Kong, Shuangyan; Yang, Chenhui; Liu, Nan; Liu, Lijuan; et al. (Frontiers in Aging Neuroscience, 2021)
Background: The value of cerebrospinal fluid (CSF) biomarkers for idiopathic normal pressure hydrocephalus (iNPH) needs to be determined. This prospective study aimed to reveal the correlation between CSF biomarkers and clinical symptoms of iNPH, and its predictive value for tap test responsiveness. Methods: Thirty-nine suspected iNPH patients were recruited, contributed qualified CSF, and accepted a tap test and unified pre- and post-test evaluation of neurological function. Results: The analysis of biomarkers from their CSF showed a decrease of tau and its phosphorylated form, especially in the tap test (+) group. In addition, the responsiveness of the tap test was also related to the number of combined symptoms (p<0.01). A correlation was also found between the end pressure or pressure difference of CSF and tap test responsiveness (p<0.05). The results of binary logistic regression analysis showed that P (tap test responsiveness) = 1/1 + e ^ - (-5.505+55.314 * ratio of p/T-tau - 1.586 * numbers of combined symptoms). The combined indicators (-5.505+0.553* percentage of p/T-tau - 1.586 * numbers of combined symptoms) gave the highest sensitivity and specificity, which were 94.12% and 72.73%, respectively. Conclusions: It may be accessed in judgment of tap test responsiveness, which is beneficial for the feasibility of clinical application.